Effect of Self-Efficacy, Work Discipline, Job Satisfaction, and Employee Engagement on Employee Performance - Putri Anggi Irawan; Akhmad Darmawan; Purnadi Purnadi; Restu Frida Utami (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the effects of work discipline, self-efficacy, job satisfaction, and employee engagement on employee performance in a manufacturing company. This research is important to understand how both psychological and behavioral factors influence performance in high-pressure and routine industrial environments. Methodology: The study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 employees of PT Royal Korindah, Purbalingga. The data were analyzed using multiple linear regression with the assistance of SPSS software. Results: The findings show that work discipline, self-efficacy, job satisfaction, and employee engagement simultaneously have a significant effect on employee performance. Partially, work discipline and employee engagement have a negative and significant effect, while self-efficacy and job satisfaction have a positive and significant effect on employee performance. Findings: The results indicate that excessive discipline and employee engagement may reduce performance, particularly in manufacturing jobs characterized by repetitive tasks and high work pressure. Novelty and Originality: This study provides new insights by revealing the potential negative impact of excessive discipline and engagement on performance in the manufacturing sector, which is rarely discussed in previous studies. Conclusion: Balanced human resource management that considers employees’ psychological conditions is essential to achieve sustainable employee performance. Type of Paper: This paper is an empirical research paper.